THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON BUSINESS ETHICS AND ITS RELATIONSHIP TO EMPLOYEE PERFORMANCE OF PT WAHANA RITEL HONDA MEDAN SUNGGAL - Boy Sihaloho; Ridhya Dwi Andriani (SEAN Institute, 2023)
The research objective to be achieved is to determine the influence of transformational leadership on business ethics and its relationship to employee performance. The research population was employees of PT Wahana Ritel Honda Medan Sunggal using the entire population. Data analysis uses Structural Equation Modeling (SEM) Partial Least Square. Based on the calculation results, it shows that transformational leadership has a significant effect on business ethics and employee performance. The direct influence of transformational leadership on employee performance is 0.50, while the influence on business ethics is 0.60. The influence of business ethics on employee performance is 0.45. Meanwhile, the overall influence of transformational leadership and business ethics is 0.67 or 67%. This shows that changes in employee performance can be explained by 67% of transformational leadership and business ethics, while the remaining 33% is influenced by other variables not examined in this research.